Fatigue performance of transverse welded attachment of high-strength structural steel series. (January 2023) - Tong, Lewei; Niu, Lichao; Ren, Zhenzhen; Zhao, Xiao-Ling
Abstract: This study presents an experimental investigation of the fatigue performance of non-load-carrying transverse fillet-welded attachments made of high-strength steel (HSS). Four typical HSSs were selected, with steel yield strength of 460 MPa, 550 MPa, 690 MPa, and 960 MPa. A total of 88 high-cycle fatigue tests were conducted. Based on the analysis of the morphological details of the fracture surfaces and the failure modes, three different methods for fatigue assessment, such as the nominal stress method, the effective notch stress method and the strain energy density method, were applied to directly compare the fatigue performance of HSS and conventional strength steel (CSS, with a yield strength of approximately 235–355 MPa). HSS transverse fillet-welded attachments have demonstrated excellent fatigue resistance compared with specifications (FAT 80) in the design codes by using the nominal stress method, the natural slope of the S – N curves is nearly 4.0, rather than 3.0 prescribed in the current design codes for fatigue assessment of welded structures. For the notch stress method, HSS transverse fillet-welded attachments show a greater increase in fatigue life for low notch stress ranges (approximately Δ σ k ≤ 400 MPa). However, for high notch stress ranges (approximately Δ σ k > 400 MPa), the increase in fatigue life is limited. The results with the strain energy density method are similar to those with the notch stress method. Highlights: Fatigue tests of transverse fillet-welded attachments made of high-strength structural steel (HSS) series were carried out. Fracture surface features and typical failure modes were compared to reveal the crack-propagation behaviors. Three different methods for fatigue assessment were applied to compare the fatigue performance of various HSS. Key factors affecting the fatigue properties of HSS transverse attachments were discussed in detail.